Blood Levels of Macrophage Migration Inhibitory Factor after Successful Resuscitation from Cardiac Arrest - Stoppe, Christian; Fries, Michael; Rossaint, Rolf; Grieb, Gerrit; Coburn, Mark; Simons, David; Brücken, David; Bernhagen, Jürgen; Pallua, Norbert; Rex, Steffen (PLOS ONE, 2012)
Introduction Ischemia-reperfusion injury following cardiopulmonary resuscitation (CPR) is associated with a systemic inflammatory response, resulting in post-resuscitation disease. In the present study we investigated the response of the pleiotropic inflammatory cytokine macrophage migration inhibitory factor (MIF) to CPR in patients admitted to the hospital after out-of-hospital cardiac arrest (OHCA). To describe the magnitude of MIF release, we compared the blood levels from CPR patients with those obtained in healthy volunteers and with an aged- and gender-matched group of patients undergoing cardiac surgery with the use of extracorporeal circulation. Methods Blood samples of 17 patients with return of spontaneous circulation (ROSC) after OHCA were obtained upon admission to the intensive care unit, and 6, 12, 24, 72 and 96 h later. Arrest and treatment related data were documented according to the Utstein style. Results In patients after ROSC, MIF levels at admission (475.2±157.8 ng/ml) were significantly higher than in healthy volunteers (12.5±16.9 ng/ml, p<0.007) and in patients after cardiac surgery (78.2±41.6 ng/ml, p<0.007). Six hours after admission, MIF levels were decreased by more than 50% (150.5±127.2 ng/ml, p<0.007), but were not further reduced in the subsequent time course and remained significantly higher than the values observed during the ICU stay of cardiac surgical patients. In this small group of patients, MIF levels could not discriminate between survivors and non-survivors and were not affected by treatment with mild therapeutic hypothermia. Conclusion MIF shows a rapid and pronounced increase following CPR, hence allowing a very early assessment of the inflammatory response. Further studies are warranted in larger patient groups to determine the prognostic significance of MIF. Trial Registration ClinicalTrials.gov NCT01412619